Understanding Wellbeing Among College Music Students and Amateur Musicians in Western Switzerland - Antonini Philippe, Roberta; Kosirnik, Céline; Vuichoud, Noémi; Williamon, Aaron; von Roten, Fabienne Crettaz (Frontiers in Psychology, 2019)
Musical performance requires the ability to master a complex integration of highly specialized motor, cognitive and perceptual skills developed over years of practice. It often means also being able to deal with a large amount of pressure within dynamic environments. Consequently, many musicians suffer from health-related problems and have a large number of physical and psychological complaints. Research has shown that making music can present challenges for musicians’ wellbeing. Therefore, our research aims to evaluate and analyze the wellbeing of two distinct groups of respondents, college music students compared with amateur musicians in the French-speaking part of Switzerland, this second group serving as our comparison group. This article presents the results of a sample of 126 musicians (mean age ± SD = 22.4 ± 4.5 years, 71 male). The wellbeing was assessed through the World Health Organization Quality of Life-BREF questionnaire evaluating two general measures, Quality of Life and General health, and four specific dimensions, Physical health, Psychological health, Social relationships and Environment. The respondents’ Quality of Life was high on each measure: median scores were higher than 4 for the first two measures and higher than 70 for the four specific dimensions. Among the dimensions, respondents had the highest mean score for Social relationships and Physical health (74.0 and 73.8, respectively) and, finally, on Psychological health (70.3). Our overview of musicians’ wellbeing in Western Switzerland underlines the importance of helping musicians to be aware of their health in order to take care of themselves. This research offers an important insight into musicians’ health and point out the importance of involving different actors (teachers, administrators or support staff) to promote their wellbeing and empower musicians.